Primary synovial sarcoma of the thyroid gland: a CARE compliant case report and literature review - Ren, Chutong; Li, Yashan; Huang, Jiangsheng; Liu, Sushun; Cao, Zhexu; Jiang, Qin; Lin, Xiang; Ye, Fei; Gong, Yi (Frontiers in Medicine, 2023)
Rationale: Synovial sarcoma is a subtype of soft tissue sarcoma. Synovial sarcoma in head and neck region is relatively unusual. Primary synovial sarcoma of the thyroid gland (PSST) is firstly reported in 2003 by Inako Kikuchi. PSST is extremely rare with only 15 cases documented globally. PSST shows rapid disease progression and relatively poor prognosis. However, the diagnosis and therapy are challenging for clinical surgeons. Here in this article, we reported the 16th PSST case and review the PSST cases globally for further clinical application. Patient concerns: The patient referred to us because of gradually worsened dyspnea and dysphagia for 20 days. Physical examination showed a 5×4cm mass with clear boundary and good mobility. Contrast-enhanced ultrasonography (CEUS) and computed tomography (CT) show a mass in the isthmus of the thyroid gland. Imageology diagnose tends to be a benign thyroid nodule. Diagnosis: After surgery, histopathology, immunohistochemistry and fluorescence in situ hybridization indicated the mass to be primary synovial sarcoma of the thyroid gland with no local and distant metastasis. Interventions: The patient underwent total thyroidectomy and dissected the lymph nodes in the central compartment. This patient received postoperative chemotherapy (combination of ifosfamide and epirubicin for 5 cycles). Patients tolerated chemotherapy well. No recurrence was found during 9 months follow-up. Lessons: Although PSST is an extremely rare disease, we should raise our awareness when we encounter a rapid growing, cystic-solid mixed thyroid mass with neck compression symptoms to avoid misdiagnose. Intraoperatively, surgeons should refine surgical procedures to avoid capsular rupture and tumor local implantation metastasis. Intraoperative frozen section pathology is necessary sometimes especially when diagnose could not be established before surgery.